Learning and networking at the CGIAR Booth in Accra, Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CGIAR organised a an interactive booth at the Africa Agriculture Science Week (AASW) in Accra, Ghana 15-20 July. In the evening, CGIAR also organised a networking session, for people to learn more about the ongoing research and activities.